2019
DOI: 10.1002/iub.2190
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of rosiglitazone, a peroxisome proliferator gamma agonist on adriamycin‐induced cardio toxicity via suppressing oxidative stress and apoptosis

Abstract: We investigated the rosiglitazone (RSG) effect on adriamycin (ADM)‐induced cardio toxicity in experimental animals. Forty adult Wistar male rats were separated into four groups as follows: normal control; RSG (10 mg/kg)‐treated; ADM (10 mg/kg)‐administered; and ADM (10 mg/kg) + RSG (10 mg/kg)‐treated. Serum lipid level, different biochemical biomarkers, histological analysis, and nuclear factor erythroid 2‐related factor/heme oxygenase‐1 (Nrf2/HO‐1), Caspase 3, B‐cell lymphoma 2 (Bcl‐2), and Bax gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Rosiglitazone and pioglitazone belong to the thiazolidinedione class of hypoglycemic agents and are recognized as PPAR-γ agonists. These two drugs were not only able to enrich GSH contents and GPX activity and defend the heart against oxidative stress but also prevented DOX or I/R-induced myocardial injury [214][215][216][217]. Some clinical studies have shown that pioglitazone treatment (30 mg/day, P.O for 4 weeks) exhibits antioxidant properties in diabetic patients, as reflected by a decrease in MDA [218,219].…”
Section: Glutathione System Activatormentioning
confidence: 99%
“…Rosiglitazone and pioglitazone belong to the thiazolidinedione class of hypoglycemic agents and are recognized as PPAR-γ agonists. These two drugs were not only able to enrich GSH contents and GPX activity and defend the heart against oxidative stress but also prevented DOX or I/R-induced myocardial injury [214][215][216][217]. Some clinical studies have shown that pioglitazone treatment (30 mg/day, P.O for 4 weeks) exhibits antioxidant properties in diabetic patients, as reflected by a decrease in MDA [218,219].…”
Section: Glutathione System Activatormentioning
confidence: 99%
“…Ferroptosis has been reported to be associated with damage to the brain and heart. 15,16 Thiazolidinediones appear to work preventively rather than therapeutically, under this condition, we injected rosiglitazone into the abdominal cavity 30 min before the operation, 30 min after the operation and 4 h after the operation, thus allowing sufficient time for proper phospholipid remodelling. The results showed that intraperitoneal injection of rosiglitazone reduced brain edema and ROS accumulation in SBI rats (Figure 2C).…”
Section: Discussionmentioning
confidence: 99%
“…Acute phase proteins orosomucoid 1 and follistatin-like 1 reduce the adhesion of Nrf2 to Keap1 in doxorubicin-induced cardiomyocytes, thereby promoting the nuclear translocation of Nrf2 and reducing the excessive accumulation of ROS in cardiomyocytes, thereby exerting antioxidant and anti-apoptotic effects [ 28 , 79 , 125 , 128 , 192 – 195 ]. Numerous other agonists and inhibitors, such as lipocalin agonists and phosphatase inhibitors, have been demonstrated in the available literature to promote doxorubicin-induced nuclear expression of Nrf2 in cardiomyocytes, thereby reducing the generation of oxidative stress in cardiomyocytes to reduce damage to the mitochondrial membrane of cardiomyocytes and thereby ameliorating apoptosis and oxidative stress in cardiomyocytes [ 14 , 31 , 196 , 197 ].…”
Section: Targeting Nrf2 For Doxorubicin-induced Cardiotoxicitymentioning
confidence: 99%